2018
DOI: 10.1016/j.ehj.2017.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Impact of fractional flow reserve on decision-making in daily clinical practice: A single center experience in Egypt

Abstract: BackgroundFractional flow reserve (FFR) is the reference standard for the assessment of the functional significance of coronary artery stenoses, but remains underutilized. Our aims were to study whether FFR changed the decision for treatment of intermediate coronary lesions and to assess the clinical outcome in the deferred and intervention groups.MethodsIn this retrospective study, coronary angiograms of patients with moderately stenotic lesions (40–70%) for which FFR was performed were re-analyzed by three e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…This present research revealed that the lesion length and stenosis severity predicted lower FFR. FFR calculation is therefore sufficient to classify intermediate LM stenosis patients in whom excellent results can be associated with revascularization postpone, and this is in accordance with Elfaramawy et al (12) .…”
Section: Discussionsupporting
confidence: 86%
“…This present research revealed that the lesion length and stenosis severity predicted lower FFR. FFR calculation is therefore sufficient to classify intermediate LM stenosis patients in whom excellent results can be associated with revascularization postpone, and this is in accordance with Elfaramawy et al (12) .…”
Section: Discussionsupporting
confidence: 86%
“…However, FFR remains the gold standard for the evaluation of the functional relevance of coronary artery stenosis. 28,29 In a group of STEMI patients with multivessel disease, revascularized with culprit-only PCI, FFR measured in the non-culprit lesions immediately after successful primary PCI showed a nonlinear and inverse risk continuum of MACE. 30,31,34,35…”
Section: Discussionmentioning
confidence: 99%